EXPLORING THE TAMASYA (“TAKALLAM LI AJLI SA‘ĀDAH”) PROGRAM: A QUALITATIVE STUDY OF HOW SPEAKING-HABIT INNOVATION FOSTERS STUDENTS’ INTEREST IN LEARNING ARABIC AT MTs MA’ARIF TIENG, WONOSOBO - Siti Nurul Anjani Safitri; Asep Sunarko; Ahmad Zuhdi; Moh Ali Khusein; Qurroti A’yun (UIN Maulana Malik Ibrahim Malang, 2026)
This qualitative descriptive study examines the TAMASYA (Takallam li Ajli Sa‘ādah) program at MTs Ma’arif Tieng, Wonosobo, and explores how it nurtures students’ interest in learning Arabic. Data were collected through in-depth interviews with an Arabic teacher, observations of activities in classrooms and school spaces, and analysis of program documents and learning materials. Data were analyzed iteratively through reduction, display, and conclusion drawing; credibility was enhanced through triangulation. Findings show that TAMASYA runs as a sustained routine: daily greetings and functional expressions, thematic mufradāt, simple hiwār, istimā‘–taqlīd, and language games, reinforced by weekly vocabulary and partial Arabic classroom instructions. Implemented inside and outside class and aligned with lesson content, the program provides meaningful exposure that lowers anxiety, increases participation, and strengthens confidence to produce simple utterances and respond to Arabic instructions. Consequently, Arabic is perceived as more relevant and less intimidating, supporting higher motivation and interest. It emphasizes consistency, enjoyment, and humane feedback in speaking practice.